2013
DOI: 10.1128/cvi.00481-12
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Region of Difference (RD) 2 Antigen Rv1985c and RD11 Antigen Rv3425 Have the Promising Potential To Distinguish Patients with Active Tuberculosis from M. bovis BCG-Vaccinated Individuals

Abstract: e Antigens encoded in the region of difference (RD) of Mycobacterium tuberculosis constitute a potential source of specific immunodiagnostic antigens for distinguishing tuberculosis (TB) infection from BCG vaccination. We evaluated the diagnostic potential of specific T-cell epitopes selected from two immunodominant antigens, Rv1985c and Rv3425, from RD2 and RD11, respectively, on the basis of epitope mapping, in TB patients and BCG-vaccinated healthy individuals. Using a whole-blood gamma interferon release a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
(67 reference statements)
2
10
0
Order By: Relevance
“…4). These results were consistent with those of the RD11-encoded antigen Rv3245 (19), which is now in further and preclinical studies in China (9,(36)(37)(38). These data indicated that IFA may be used as one of the most optimal adjuvants for Rv3117-based vaccine studies in animal models.…”
Section: Discussionsupporting
confidence: 84%
“…4). These results were consistent with those of the RD11-encoded antigen Rv3245 (19), which is now in further and preclinical studies in China (9,(36)(37)(38). These data indicated that IFA may be used as one of the most optimal adjuvants for Rv3117-based vaccine studies in animal models.…”
Section: Discussionsupporting
confidence: 84%
“…The addition of the novel peptides to the QFT resulted in a significant increase in the IFN-γ release in active TB, without altering specificity, and also in the BCG-vaccinated control population. This is consistent with previous data in the literature indicating that the addition of other non-RD1 proteins to QFT can result in an increase of the test performance [4,5], as also observed in the changes implemented in the QFT test versions [1].…”
Section: The Intracellular Expression Of Ifn-γ In Cd4supporting
confidence: 93%
“…To improve the performance of the IGRAs, addition of MTB antigens TB7.7, Rv3425 and EsxV to the current antigen cocktail has already been attempted [4,5]. Following a similar strategy, we evaluated the addition of six novel peptides to the QFT antigen cocktail to improve the diagnostic performance in terms of accuracy and dynamic range of interferon (IFN)-γ level in active TB patients.…”
Section: Quantiferon-tb Performance Enhanced By Novel Mycobacterium Tmentioning
confidence: 99%
See 1 more Smart Citation
“…PE/PPE proteins located in RD regions are considered to be the most promising candidates for TB vaccine development and diagnostic agents, especially secreted antigens (Abraham et al, 2018). Rv3425 (PPE57), which locates in the RD11 region and induces macrophage activation by augmenting the expression of MHC-II and pro-inflammatory cytokines (TNF-α, IL-6, and IL-12p40), has been confirmed with the potential to distinguish patients with active TB via QFT assay (Wang et al, 2013; Losi et al, 2016) and for use as an antigen for therapeutic or protective vaccine design (Xu et al, 2014; Yang et al, 2015). In this study, Rv1768 evoked a significantly high level of IFN-γ in H37Rv-infected mice, but not BCG-infected or normal mice.…”
Section: Discussionmentioning
confidence: 96%